IMPROVING THE STUDENTS’ SPEAKING ABILITY THROUGH PARTICIPATION POINT SYSTEM (PPS) METHOD - Andi Asri Jumiati; A Sri Asrina (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2013)
This research was aimed at finding out the improvement of students’ speaking accuracy and fluency through Participation Point System (PPS) Method in teaching speaking. The research method used was class action research design consisting of 4 stages, namely planning, action observation, and reflection. It had 2 cycles. The research was implemented by the Tenth-grade students of SMA PGRI Sungguminasa 2011/2012. The researcher took 26 students as the subject of the research. The researcher taught speaking English using PPS Method. The data were gathered after scoring the students’ speaking ability on both accuracy (vocabulary and grammar) and fluency (smoothness) through diagnostic test and test of the cycle I and II. The research findings showed that the mean score of the students’ speaking diagnostic test was 3.7 as categorized poor (low ability) while the mean score of the students’ speaking test in cycle I was 5.2. It had a significant progress but the result still did not reach the determined standard score 6.5, so the research has proceeded to the cycle II that the researcher gained the mean score 7 as categorized well. It showed that the latest progress in the cycle II had reached beyond the determined standard score and there was a significant improvement on the tenth-grade students’ speaking ability on both accuracy (vocabulary and grammar) and fluency (smoothness) in the English teaching using Participation Point System Method at SMA PGRI Sungguminasa 2011/2012.Keywords: Improving, Speaking, Participation, Point, System.